2005
DOI: 10.1152/ajplung.00336.2004
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human VEGF treatment enhances alveolarization after hyperoxic lung injury in neonatal rats

Abstract: -VEGF signaling inhibition decreases alveolar and vessel growth in the developing lung, suggesting that impaired VEGF signaling may contribute to decreased lung growth in bronchopulmonary dysplasia (BPD). Whether VEGF treatment improves lung structure in experimental models of BPD is unknown. The objective was to determine whether VEGF treatment enhances alveolarization in infant rats after hyperoxia. Two-day-old Sprague-Dawley rats were placed into hyperoxia or room air (RA) for 12 days. At 14 days, rats rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
131
1
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 188 publications
(153 citation statements)
references
References 47 publications
14
131
1
7
Order By: Relevance
“…9 -11 Blocking VEGF signaling disrupts postnatal alveolar development, [12][13][14] and VEGF gene therapy can partially protect the developing rat lung against hyperoxia. 15,16 Besides VEGF, the number of circulating endothelial cell precursors found in blood and lung is reduced in neonatal mice exposed to hyperoxia 17 and, when restored, can attenuate murine models of BPD. 18,19 Collectively, a large body of data suggests that alveolar simplification and pulmonary hypertension seen in infants dying with BPD may be caused by oxidative stress disrupting microvascular development.…”
mentioning
confidence: 99%
“…9 -11 Blocking VEGF signaling disrupts postnatal alveolar development, [12][13][14] and VEGF gene therapy can partially protect the developing rat lung against hyperoxia. 15,16 Besides VEGF, the number of circulating endothelial cell precursors found in blood and lung is reduced in neonatal mice exposed to hyperoxia 17 and, when restored, can attenuate murine models of BPD. 18,19 Collectively, a large body of data suggests that alveolar simplification and pulmonary hypertension seen in infants dying with BPD may be caused by oxidative stress disrupting microvascular development.…”
mentioning
confidence: 99%
“…Intriguingly, some of these changes are permanent, as normal lung structure and function are not restored when newborn animals are returned to room air (9)(10)(11). Hyperactive airways with increased thickness of the underlying smooth muscle have also been reported in 21-day-old rats exposed to and recovered from greater than 95% oxygen (12,13).…”
mentioning
confidence: 99%
“…Nrp1 may modulate the balance between VEGF and Sema3 signaling to alter cell proliferation and death in nonepithelial cell types (17,26). Both Nrp1 ligands, VEGF, and Sema3A, have independently been shown to contribute to alveolar septation (24,(27)(28)(29)(30) and vascular patterning (23,27,31), and human (32,33), animal (34)(35)(36)(37), and in vitro (38) studies support a possible role for VEGF in protection from acute lung injury and preservation of alveolar cell survival (39). Of note, it was shown that expression of Nrp1 protein was reduced in the lungs from smokers with spirometric evidence of COPD compared with smokers who had normal lung function and nonsmoking control subjects (40).…”
mentioning
confidence: 99%